Examining Justice in Social Studies Research - J. Spencer Clark; Steven P. Camicia (Pedagogy & (Im)Possibilities across Education Research, 2017)
Our article is an extension of a project involving a content analysis of two social studies journals, Theory and Research in Social Education (TRSE) and The Social Studies. We performed an analysis on all articles in these journals from 2006-2016. Our findings from the analysis indicated a narrow frame of perspectives related to epistemologies and methodologies, and an increasing interest in examining a range of researcher and participant positionalities. We interpreted the range of perspectives in social studies journals in light of the possible impact upon democratic education and social justice through Sen’s (2009) framework for theorizing justice. We illustrate aspects of this framework by presenting positionality and autoethnography as methods for increasing epistemologies and perspectives in social studies education and research.
Keywords: Positionality; Autoethnography; Justice; Amartya Sen; Social Studies Education